Prediksi harga minyak mentah WTI dengan menggunakan metode Garch dalam ancaman perang dunia III - Lestari, Tri; Andriani, Putri; Gunawan, Didik; Cahyadi, Willy (Journal of Economics Research and Policy Studies, 2025)
This research aims to forecast fluctuations in the price of West Texas Intermediate (WTI) crude oil within the potential threat of World War III by utilizing the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) method. Using daily closing price data of WTI crude oil from January 2022 to March 2025, consisting of 850 observations, this study employs the ARIMA-GARCH model to capture the patterns and volatility of the time series data. Based on the conducted analysis, it is concluded that the ARIMA (2,1,2) and GARCH (1,1) models demonstrate optimal performance, with a MAPE value of 13.71%, indicating a good prediction accuracy level. The forecast for the next two years shows a trend of price increases starting from Q2 2025 through Q4 2027. This research demonstrates how geopolitical tensions, particularly the Russia-Ukraine war and Middle Eastern Conflicts, can affect global oil price volatility while highlighting the GARCH model’s effectiveness in capturing heteroskedasticity in highly fluctuating financial data.